The use of remote sensing for monitoring Posidonia oceanica and Marine Protected Areas: A systemic review - Appolloni, Luca; Buonocore, Elvira; Russo, Giovanni Fulvio; Franzese, Pier Paolo (Ecological Questions, 2020)
Posidonia oceanica is a priority habitat (Habitat Directive 92/43/CEE) that needs to be protected by conservation tools such as Marine Protected Areas (MPAs). Remote Sensing (RS) is a useful tool allowing for mapping seagrass meadows and other important marine habitats. In this study, we explore the global scientific literature on RS applied to both P. oceanica and MPAs tracking its evolution and trends by applying network analysis to bibliometric science. The software VOSviewer was used to create maps based on network data of scientific publications displaying relationships among authors and countries. In addition, specific keywords were used to explore the co-occurrence of different terms characterizing the application of RS in marine science. Results showed that France is the main country publishing on RS applied to Posidonia oceanica while Pergent Gérard and Pergent-Martini Cristine resulted the top authors. The co-occurrences analysis highlighted that RS is primarily used for seagrasses mapping, while few studies are focused on their monitoring. Furthermore, investigating RS in connection with MPAs the main country resulted Australia while the top author was Andréfouet. The network map of keywords showed that RS is widely applied to MPAs to study coral reefs and their biodiversity and for mapping marine ecosystems. The use of RS for monitoring Posidonia oceanica beds and MPAs resulted a poorly explored research area, probably due to the low resolution of available data determining large scale habitat mapping. In conclusion, we maintain that RS applications can provide useful information about the effects of local human activities and global climate change on marine ecosystems